Mesotherapy with hyaluronic acid solutions enriched by amino acids in the neck area: open-label uncontrolled, monocentric study - Scarano, Antonio; Qorri, Erda; Sbarbati, Andrea; Gehrke, Sérgio Alexandre; Marchetti, Marco; Desiderio, Vincenzo; Amuso, Domenico; Tari, Sergio (Journal of cosmetic and laser therapy, 2025)
The process of face aging is characterized by various signs, including nasolabial folds, sagging and hollowing, all of which worsen with age. In some subjects, this phenomenon is exacerbated by sun exposure, bad diet, genetic factor, pollution, etc. This remains a great concern as it impacts physiologically and psychologically on patient quality of life. The intradermal solution based on bio-fermentative HA is indicated for correction of skin damages including rhytidosis, photoaging and skin dehydration. The present clinical investigation was designed for obtaining further clinical safety and efficacy data for the SKIN R intradermal solution for the treatment of skin damages. The efficacy of the treatments was assessed by measuring the pH, assessment of sebometry, and hydrometry, Global Aesthetic Improvement Scale and Subject satisfaction. All 15 screened and enrolled subjects were treated with the investigational device at least once. All subjects who were assessed had a neck photo taken at visits 1 and 2. The subjects' judgment of appearance after treatment changed with time, however, by the termination of the study on Day 60, 33.3% of subjects still considered their appearance very much improved, and 46,6% still considered their appearance much improved. The assessment of "satisfaction with treatment" was very high by the majority of subjects. No major adverse event was recorded. In conclusion, SKIN R is safe and well-tolerated and is effective in the treatment of skin damage.